The Ethics of Zero-Day Exploits--The NSA Meets the Trolley Car. - WICKER, STEPHEN B. (Communications of the ACM, 2021)
The article discusses the ethics of U.S. government employees concerning the collection of computer software bugs and ransomware vulnerabilities. It discusses the U.S. National Security Agency (NSA), public policy education concerning stockpiling, and balanced policies about what are referred to as zero-day actions versus threats to the public.